An Enhanced Anti-Tumor Response by Using Bacterial Magnetosomes Gene Administration Platform - Tang, Yishu; Zhou, Chunxia; Ma, Wenbo; Wang, Dongmei; Zhang, Shuren (Archives of Clinical and Biomedical Research, 2018)
DNA vaccination is an effective way to induce specific immunity. In our study, we used magnetosomes (bacterial magnetic particles, BMPs) as the vehicle of a DNA complex of a secondary lymphoid tissue chemokine, human papillomavirus type E7 (HPV-E7) and Ig-Fc fragment (pSLC-E7-Fc) to produce a gene vaccine (BMP-V) for tumor immunotherapy. In a mouse tumour model, intramuscular injection of BMP-V plus magnetic exposure induced E7- specific immunity eliciting to tumor inhibition. Taken together, these results demonstrated that BMP could be applied as a DNA vehicle to induce specific immune effect.